2005
DOI: 10.2337/diacare.28.5.1022
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Index, Glycemic Load, Cereal Fiber, and Plasma Adiponectin Concentration in Diabetic Men

Abstract: OBJECTIVE -Adiponectin may improve insulin sensitivity, reduce inflammation, and ameliorate glycemic control. However, few studies have evaluated dietary predictors of plasma adiponectin levels, especially among subjects with type 2 diabetes.RESEARCH DESIGN AND METHODS -To examine the associations of dietary glycemic load, glycemic index, and fibers with plasma adiponectin levels, we conducted a crosssectional analysis in 780 diabetic men from the Health Professionals' Follow-up Study. Dietary information was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
111
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 39 publications
11
111
2
5
Order By: Relevance
“…Ma et al (2006) observed an inverse association between the intake of total DF (separately for soluble and insoluble fibre) and CRP concentrations in both cross-sectional and longitudinal analyses but could not tease apart their effects because they are part of the same foods. Epidemiological (Salmeron et al, 1997;Schulze et al, 2004b) and experimental (Qi et al, 2005(Qi et al, , 2006) studies indicate a stronger inverse association of cereal fibre with type 2 diabetes, coronary heart disease and lower CRP concentrations than other types of fibre; however, the mechanisms are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al (2006) observed an inverse association between the intake of total DF (separately for soluble and insoluble fibre) and CRP concentrations in both cross-sectional and longitudinal analyses but could not tease apart their effects because they are part of the same foods. Epidemiological (Salmeron et al, 1997;Schulze et al, 2004b) and experimental (Qi et al, 2005(Qi et al, , 2006) studies indicate a stronger inverse association of cereal fibre with type 2 diabetes, coronary heart disease and lower CRP concentrations than other types of fibre; however, the mechanisms are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the short term (72 h), insoluble fibre (31.2 g) has been shown to improve wholebody insulin sensitivity in obese and overweight women (Weickert et al, 2006). In a cross-sectional analysis of 780 diabetic men, high glycaemic index and glycaemic load were associated with lower concentrations of plasma adiponectin (Qi et al, 2005) and positive associations between cereal fibre and plasma adiponectin were observed (Esposito et al, 2003b;Richter et al, 2004). In insulin-resistant states, insulin has a pro-inflammatory effect producing more cytokines (Fernandez-Real and Ricart, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Secreted IL-6, intracellular IL-6, and IL-6 mRNA were found to be significantly increased with hyperglycemia (P < 0.001) [48]. In addition, Qi and colleagues found that diets high in fiber may increase plasma adiponectin concentrations in diabetic patients [49] and adiponectin has been found to have profound anti-inflammatory effects [50].…”
Section: Discussionmentioning
confidence: 99%
“…As overweight is related to decreased insulin sensitivity (Fung et al, 2003), this may suggest that magnesium is inversely associated with colorectal cancer risk through improved insulin sensitivity. Recently, magnesium intake was found to be associated with increased levels of adiponectin, which may improve insulin sensitivity (Qi et al, 2005); adiponectin was inversely associated with colorectal cancer risk among men (Wei et al, 2005).…”
Section: Discussionmentioning
confidence: 99%